Robust trajectory tracking with non-singular terminal sliding mode control of a mobile manipulator - Shankar J. Gambhire; Dondapati Ravi Kishore; Pandurang S. Londhe; Sushant N. Pawar (Institute of Advanced Engineering and Science, 2022)
This effort addresses and uses a robust-trajectory-tracking control system for kinematically redundant location tracking of a mobile manipulator (mobman) in its task space in the presence of parameter uncertainties and external disturbances. It consists of a serial manipulator with four degrees of freedom (DOF) fixed on three DOF mobile bases. A robust tracking control is achieved using the configuration of a non-singular terminal sliding mode (NSTSM) control for the entire non-linear model of a mobman. Because of the non-linear added term in the linear sliding surface, which reflects in the non-linear sliding mode known as terminal sliding mode (TSM), this control preparation satisfies systems states finite time convergence. Similarly, conventional terminal sliding mode control (CTSMC) entail singularity trouble, which is tackled by the control scheme. (Computer based) simulations are used to demonstrate the convenience, feasibility, and robustness of given techniques.